The recurrence and mortality risk in Luminal A breast cancer patients who lived in high pollution area - Pimwarat Srikummoon; Patrinee Traisathit; Wimrak Onchan; Chagkrit Ditsatham; Natthapat Thongsak; Nawapon Nakharutai; Salinee Thumronglaohapun; Titaporn Supasri; Phonpat Hemwan; Imjai Chitapanarux (PLoS ONE, 2025)
Luminal A is the most common subtype of breast cancer and has the best prognosis comparing to the others. The association between air pollution and survival of breast cancer have been reported but not specific to this subtype. We examined pollutant distributions over a decade in upper Northern Thailand, the area of high average annual particulate matter levels, and their impact on the mortality and recurrence risks of patients with luminal A breast cancer. Retrospective data of 1,305 luminal A breast cancer patients diagnosed from 2003 to 2018 were enrolled to this study. Cox proportional hazard models were used to identify factors associated with mortality and recurrence risks including all known risk factors and the annually averaged concentrations of pollutants. On multivariable analysis; metastatic stage (adjusted hazard ratio (aHR) =10.50; 95% confidence interval (95%CI): 7.23–15.25), smoking history (aHR = 1.72; 95% CI: 1.14–2.60), and age ≥ 50 years old (aHR = 1.46; 95% CI: 1.13–1.90) were significant factors influencing mortality risk. Factors contributing to recurrence risk included metastatic stage (aHR) 4.96 (95% CI: 2.78–8.83) and exposure to the time-updated local concentration of PM 10 > 55 µg/m 3 (aHR = 1.68; 95% CI: 1.16–2.45). Exposure to air pollutants is one of the detrimental factors affected to recurrence and mortality in luminal A subtype breast cancer.